2014
DOI: 10.1007/s11571-014-9302-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects on hypothalamus when CPG is fed back to basal ganglia based on KIV model

Abstract: The KIV model approximates the operation of the basic vertebrate forebrain together with the basal ganglia and motor systems. In KIV model, the hypothalamus and the basal ganglia which are two important parts in the midline forebrain are closely associated with the locomotion. The CPG model with time delay is established in this paper and the stability of this CPG model is discussed. The CPG output is treated as the proprioception and fed back to the basal ganglia. We focus on the effects on the hypothalamus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Comparing with previous studies [19], [27], [28], the proposed model combining the fractional order CPG and the NMM has considerable dynamic characteristics that could help the researchers to derive the relation between the motor cortex and the locomotion. The dynamic properties of this model show that the NMM and the fractional order CPG states could be formed by adjusting its parameters.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Comparing with previous studies [19], [27], [28], the proposed model combining the fractional order CPG and the NMM has considerable dynamic characteristics that could help the researchers to derive the relation between the motor cortex and the locomotion. The dynamic properties of this model show that the NMM and the fractional order CPG states could be formed by adjusting its parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Kerkman et al [26] used network analysis to investigate the relationship between anatomical and functional connectivity. The relation between the neural network and the integer order CPG was studied in the literature [19], [27], [28]. In this paper, the coupling model between the fractional order CPG and the motor cortex is built and the relationship is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although the mammalian locomotion networks have been widely studied, understanding the coupling association in these networks is still an open problem (Kiehn 2016;Roberts et al 2012). In addition, the relationship between the CPG and the motor cortex has been explored in earlier studies based on the integral-order models (Lu et al 2015;Lu and Tian 2014) and the fractional-order ones (Lu 2020). The previous investigations showed that there exists parameters space which can make the synchronization of the motor cortex optimum when the CPG is added into the motor cortex.…”
Section: Introductionmentioning
confidence: 99%